2010
DOI: 10.1371/journal.pone.0015601
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ca2+-Activated K+ Channels Limit Brain Infarction and Promote Survival

Abstract: Neuronal calcium-activated potassium channels of the BK type are activated by membrane depolarization and intracellular Ca2+ ions. It has been suggested that these channels may play a key neuroprotective role during and after brain ischemia, but this hypothesis has so far not been tested by selective BK-channel manipulations in vivo. To elucidate the in vivo contribution of neuronal BK channels in acute focal cerebral ischemia, we performed middle cerebral artery occlusion (MCAO) in mice lacking BK channels (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 58 publications
0
41
1
Order By: Relevance
“…These results suggest that BK channels, though involved in leptin-induced protection, do not mediate NMDA-induced damage. By contrast, Liao et al (2010) showed greater neurotoxicity by intra-cerebral injection of NMDA in Slo 1 −/− mice when compared to Slo 1 +/+ mice; however, it should be emphasized that, in our in vitro model, the extracellular concentrations of endogenous glutamate are unlikely to achieve the high neurotoxic levels observed in the intact tissue in vivo during NMDA-induced neurodegeneration.…”
Section: Discussioncontrasting
confidence: 58%
“…These results suggest that BK channels, though involved in leptin-induced protection, do not mediate NMDA-induced damage. By contrast, Liao et al (2010) showed greater neurotoxicity by intra-cerebral injection of NMDA in Slo 1 −/− mice when compared to Slo 1 +/+ mice; however, it should be emphasized that, in our in vitro model, the extracellular concentrations of endogenous glutamate are unlikely to achieve the high neurotoxic levels observed in the intact tissue in vivo during NMDA-induced neurodegeneration.…”
Section: Discussioncontrasting
confidence: 58%
“…Liao et al (35) showed middle cerebral artery occlusion in mice lacking BK channels (loss-offunction) produced a significantly larger infarct volume and led to more severe neurological deficits and higher postischemic mortality than control wild type mice. Previously, we have demonstrated that PCMNs in the NA play a key role in regulating cardiac functions and that chronic intermittent hypoxia (CIH; a model for sleep apnea) may reduce PCMN control over the heart rate and induce cell loss (8,9,72,73,74).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…These negative feedback mechanisms allow BK channels to play key roles in regulating firing properties, such as repetitive firing of neurons (67), spike broadening during repetitive firing (59), and spikefrequency adaptation (26). There has also been evidence that BK channels can moderate neurotransmitter release and provide some protection against neuronal death (35,51,52,68).…”
mentioning
confidence: 99%
“…From studies in macrophages, neutrophils, and mast cells, we learned that changes in the cell membrane potential commonly precede secretory events (21,30), but the mechanisms regulating inflammatory cytokine secretion from AECs remain poorly understood. As in many biological systems, opening of Ca 2ϩ channels is thought to cause membrane depolarization and mediator secretion (35,57), whereas opening of K ϩ channels is generally associated with membrane repolarization and stabilization of the resting membrane potential (29,40). A relatively new family of K ϩ channels, two-pore-domain K ϩ (K2P) channels, are strong candidates as important regulators of the cell membrane potential (4).…”
mentioning
confidence: 99%